IMPROVING STUDENTS’ SPEAKING AND WRITING SKILLS BY USING FISHBOWL TECHNIQUE FOR THE TWELFTH GRADE OF SMK TELKOM SANDHY PUTRA BANJARBARU - Siregar, Isma Rachmadani; Luardini, Maria Arina; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2022)
This research purposes to improve student’s speaking and writing skills for the Twelfth Grade students of SMK Telkom Sandhy Putra Banjarbaru by using Fishbowl Technique. The number of subjects were 13 students who had been taught English Speaking and Writing based on the curriculum in academic year 2015/2016. The research was carried out by using Classroom Action Research (CAR) implemented by the English teacher is the researcher itself. The action was implemented into two cycles. The data were collected from the scores of pre-test, cycle one and cycle two. The result of observations and questionnaire were also calculated to give additional informations. The implementation uses Fishbowl Technique focused on : (1) the benefit of using Fishbowl as the way of technique (2) to improve the ability of the students in speaking and writing skills. A setting room is used to support implementation of modeling in this research. The results showed that students’ speaking and writing skills by using Fishbowl technique could improve the students’ ability in speaking and writing. The significant improvement of students’ achievement in speaking and writing could be seen from the increasing average score for speaking achievement from Cycle 1 to Cycle 2 that was from 67,84 to 78,00 and for writing achievement that was 70,30 to 80,61.